Evaluating the environmental and social net-worth of controlling alien plant invasions in the Inkomati catchment, South Africa - Rashid Hassan; Siphokuhle Mahlathi (Water SA, 2020)
The present study attempted to bridge some gaps in the existing literature evaluating the net economic worth of South Africa’s Working for Water (WfW) programme for eradicating invasive alien plant species (IAPS). Specifically, the study employed the social benefit-cost analysis (BCA) methodology to assess the impact of accounting for the opportunity cost of invested capital funds and treating labour as a social benefit on the social worthiness of the WfW programme in the Inkomati catchment. The study also used improved measures of the value of other ecosystem services, particularly the carbon sequestration values. Results of the social BCA provided strong empirical evidence in support of the continuation of IAPS eradication activities, as economically and socially worthwhile investment of the country’s resources. The programme generates higher net worth under lower rates of discounting future values. This confirms the importance of the water-saving benefits, which continue theoretically for ever, at zero cost to the society, as all direct and indirect financial costs cease upon completion of the eradication operations. The social net worth of the IAPS eradication programme obviously increases when expenditure on labour wages was considered a social benefit rather than a direct financial cost, even under strict project funding scenarios that require funding through private capital markets, i.e., paying commercial rates of interest. However, more strategic planning for the control of IAPS is critically important given their high cost. Challenges facing the sustainability of IAPS eradication programmes in the study area and South Africa include: raising sufficient funding from private and public sources, and introducing incentive systems to encourage higher collaboration and participation of private landowners in the currently primarily publicly driven IAPS eradication efforts. The study also suggests a number of policy and technological reforms to address the said challenges.